2014
DOI: 10.1016/j.ydbio.2014.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of DMRT1 induces the male pathway in embryonic chicken gonads

Abstract: DMRT1 encodes a conserved transcription factor with an essential role in gonadal function. In the chicken, DMRT1 is located on the Z sex chromosome and is currently the best candidate master regulator of avian gonadal sex differentiation. We previously showed that knockdown of DMRT1 expression during the period of sexual differentiation induces feminisation of male embryonic chicken gonads. This gene is therefore necessary for proper testis development in the chicken. However, whether it is sufficient to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 59 publications
6
117
0
6
Order By: Relevance
“…In this study, MPT-specific expression of Dmrt1 transcript was detected as early as stage 15, just at the onset of sex determination and the TSP. Sexually dimorphic expression of Dmrt1 preceded Amh and Sox9, two well-known factors for male sexual development, and was maintained throughout the gonadal differentiation period, which is very similar to the expression pattern of Dmrt1 in chicken (Lambeth et al, 2014;Smith et al, 2009). Interestingly, we found that Dmrt1 also exhibited early male-specific embryonic expression before the onset of gonadal sex differentiation in the Chinese soft-shelled turtle, a GSD species with ZZ/ZW sex chromosomes (W. Sun, H. Cai, G. Zhang, H. Zhang, H. Bao, L. Wang, J. Ye, G. Qian and C. Ge, unpublished).…”
Section: Discussionsupporting
confidence: 62%
“…In this study, MPT-specific expression of Dmrt1 transcript was detected as early as stage 15, just at the onset of sex determination and the TSP. Sexually dimorphic expression of Dmrt1 preceded Amh and Sox9, two well-known factors for male sexual development, and was maintained throughout the gonadal differentiation period, which is very similar to the expression pattern of Dmrt1 in chicken (Lambeth et al, 2014;Smith et al, 2009). Interestingly, we found that Dmrt1 also exhibited early male-specific embryonic expression before the onset of gonadal sex differentiation in the Chinese soft-shelled turtle, a GSD species with ZZ/ZW sex chromosomes (W. Sun, H. Cai, G. Zhang, H. Zhang, H. Bao, L. Wang, J. Ye, G. Qian and C. Ge, unpublished).…”
Section: Discussionsupporting
confidence: 62%
“…The male phenotype of tetraploid rock lizards from the genus Darevskia with ZZZW sex chromosomes and the observation of male, female or intersexual phenotypes in triploid ZZW individuals (Danielyan et al, 2008) suggest that sex determination can be based on the gene dose of Z-specific loci rather than on the dominant W-specific gene. No sexdetermining gene has been identified in sauropsids yet, with the exception of dmrt1 that is considered a strong candidate of this function in birds (Smith et al, 2009;Lambeth et al, 2014). Known sex-determining genes in vertebrates are usually homologs of genes involved in gonad differentiation (see, for example, Kikuchi and Hamaguchi, 2013;Bachtrog et al, 2014), and thus a better knowledge of the function of many genes in the ancestral mammalian X could allow the future identification of the sexdetermining gene in lacertids.…”
Section: Identification Of Putative Z-specific Genesmentioning
confidence: 99%
“…In several non-mammalian vertebrate species, they act as triggers for primary sex determination. Examples include DMY in the medaka fish Oryzias latipes (Matsuda et al, 2002;Nanda et al, 2002;Otake et al, 2010), DM-W and DMRT1 in the amphibian Xenopus laevis (Yoshimoto et al, 2008(Yoshimoto et al, , 2010 and DMRT1 in chicken (Smith et al, 2009;Lambeth et al, 2014). However, Dmrt1 has become dispensable for testis determination in mammals, as evidenced by the experimental observation that XY Dmrt1 null mutant mice are born as males with testes (Raymond et al, 2000).…”
Section: Introductionmentioning
confidence: 99%